2015
DOI: 10.2134/agronj14.0504
|View full text |Cite
|
Sign up to set email alerts
|

Cover Crop Mixtures Do Not Use Water Differently than Single‐Species Plantings

Abstract: Recent recommendations advocating the use of cover crop mixtures instead of single-species in semi-arid environments require rigorous scienti c studies. One of those stated bene ts is greatly reduced water use by cover crops grown in mixtures. e objectives of this study were to characterize soil water extraction patterns and determine water use of cover crops grown in singlespecies plantings and in a 10-species mixture and to compare cover crop water use to evaporative water loss from no-till fallow.e study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 11 publications
10
76
1
Order By: Relevance
“…Cover crops can reduce available soil‐water reserves for the following cash crop (Nielsen et al, 2015). In contrast, CC also can increase the soil water budget by decreasing evaporation, improving water infiltration, and increasing soil OM content (Dabney et al, 2001; Rawls et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cover crops can reduce available soil‐water reserves for the following cash crop (Nielsen et al, 2015). In contrast, CC also can increase the soil water budget by decreasing evaporation, improving water infiltration, and increasing soil OM content (Dabney et al, 2001; Rawls et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous benefits of CC, growers are reluctant to use CC because of concerns about reduced soil water for the following cash crop (Basche et al, 2016). Actively growing CC can reduce available soil water for the next cash crop (Blanco‐Canqui et al, 2015; Nielsen et al, 2015). However, CC also reduce water losses by increased water infiltration and reduced runoff (Blanco‐Canqui et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, water is a major limitation in the iPNW and existing research with single-and multi-species cover crops in eastern Washington and in semiarid eastern Colorado (Nielsen et al, 2015) has not found agronomic and economic benefits (Thompson and Carter, 2014;Roberts et al, 2016).…”
Section: Organic Resource Recyclingmentioning
confidence: 99%
“…Four separate crops (seeding rates and row spacing given in parentheses) were included in the analysis: corn: Zea mays L. The oat, rapeseed, and flax data were collected from field studies conducted at the United States Department of Agriculture, Agricultural Research Service (USDA-ARS) Central Great Plains Research Station (40˝09 1 N, 103˝09 1 W, 1383 m elevation above sea level) located near Akron, CO, USA [33]. The crops were planted no-till into proso millet stubble on 4 April 2013.…”
Section: Data Collectionmentioning
confidence: 99%